Permainan Edukatif Makanan Sehat dengan Kombinasi Teknik Story Telling bagi Siswa-Siswi TK Dharma Wanita 1 Persatuan Sumber Sekar sebagai Upaya Pencegahan Stunting pada Anak - Cesa, Fibe Yulinda; Ismaurasi, Marcelina Fransisca Alecia; Khoiroh, Afifatul; Sentosa, Revin Adis; Wilujeng, Lilis Lestari; Bakti, Amar Ma'ruf Stya; Hendra, Godeliva Adriani (Abdimas Indonesian Journal, 2023)
Until now, many food variants have been created by the public to attract buyers' interest. In fact, if food is not processed properly, what happens instead of being beneficial for someone is actually detrimental, one of which becomes a source of disease. Children are the target for instant food sellers who often line up and sell in front of schools. Because it tastes delicious, nowadays children are used to buying these snacks which do not necessarily have good nutritional value. If explored further, poor nutritional value will cause a serious condition in children's development called stunting. Therefore, in Sumbersekar Village there is still no education regarding healthy food, especially from an early age. For this reason, it is necessary to teach children from an early age so that they can avoid foods with low nutritional value. The target for this education is children, therefore story telling regarding healthy food will be given of course also using interactive props so that children are interested and able to remember which food categories are healthy and unhealthy. The results of this service received a very good response and according to the teacher's observations, after these teaching aids were given, children became more aware of bringing vegetables and fruit menus when bringing lunch to school. Evaluation of this service is a more structured observation, especially in the form of a questionnaire for effectiveness and monitoring changes in student behavior before and after being given the story telling service and game tools.